Colosseum [videorecording (DVD)] - Reiné, Roel; Cargill, Robert R., 1973-; Mariotti, Alexander; Scott, Campbell (Lionsgate, 2023)
Examines the rise and fall of the Roman Empire through the lens of the activities that took place in the Colosseum.